Production and characterization of bioemulsifier by Parapedobacter indicus - Devale, Anushka; Sawant, Rupali; Pardesi, Karishma; Perveen, Kahkashan; Khanam, Mehrun NIsha; Shouche, Yogesh; Mujumdar, Shilpa (Frontiers in Microbiology, 2023)
The current study evaluated Parapedobacter indicus MCC 2546 for its potential to produce a bioemulsifier (BE). Screening methods performed for BE production by P. indicus MCC 2546 showed good lipase activity, positive drop collapse test, and oil-spreading activity. Furthermore, it showed maximum emulsification activity (225 EU/ml) and emulsification index (E24 50%) at 37°C in Luria Bertani broth at 72 h with olive oil as a substrate. The optimal pH and NaCl concentration for maximum emulsification activity were 7 and 1%, respectively. P. indicus MCC 2546 lowered the surface tension of the culture medium from 59.65 to 50.42 ± 0.78 mN/m. BE produced was composed of 70% protein and 30% carbohydrate, which showed the protein–polysaccharide nature of the BE. Furthermore, Fourier transform infrared spectroscopy analysis confirmed the same. P. indicus MCC 2546 showed a catecholate type of siderophore production. This is the first report on BE and siderophore production by the genus Parapedobacter.